2017
DOI: 10.1016/j.biopsych.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Abnormalities of Attention-Deficit/Hyperactivity Disorder With Oppositional Defiant Disorder

Abstract: ADHD+ODD and ADHD-only were associated with volumetric reductions in brain areas crucial for attention, (working) memory, and decision-making. Volumetric reductions of frontal lobes were largest in the ADHD+ODD group, possibly underlying observed larger impairments in neurocognitive functions. Previously reported striatal abnormalities in ADHD may be caused by comorbid conduct disorder rather than ODD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 51 publications
5
63
2
4
Order By: Relevance
“…Some studies have investigated the effect of symptom presentation and comorbidities (especially oppositional defiant disorder and conduct disorder) in order to determine disorder specific abnormalities, but more studies are required to elicit clear‐cut conclusions.…”
Section: Structural Brain Imaging In Adhdmentioning
confidence: 99%
“…Some studies have investigated the effect of symptom presentation and comorbidities (especially oppositional defiant disorder and conduct disorder) in order to determine disorder specific abnormalities, but more studies are required to elicit clear‐cut conclusions.…”
Section: Structural Brain Imaging In Adhdmentioning
confidence: 99%
“…Interestingly, some recent studies did not assess (Greven et al, 2015;Hoogman et al, 2017) or did not find cerebellum alterations (Noordermeer et al, 2017; for a meta-analysis see also Frodl & Skokauskas, 2012), while others showed increased gray matter concentration of the cerebellum in CD (De Brito et al, 2009). Interestingly, some recent studies did not assess (Greven et al, 2015;Hoogman et al, 2017) or did not find cerebellum alterations (Noordermeer et al, 2017; for a meta-analysis see also Frodl & Skokauskas, 2012), while others showed increased gray matter concentration of the cerebellum in CD (De Brito et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed, that disentangle the specific contribution of ODD versus CD (Noordermeer et al, 2016;Noordermeer et al, 2017) and systematically compare ADHDonly, ADHD with comorbid ODD or with comorbid CD and the pure forms of ODD and CD. Due to the small size of the ADHD+ODD/CD-group, we could not differentiate between ODD and CD alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating this is the unclear impact of comorbidities on neuroanatomical differences seen in ADHD (10). In their neuroimaging study addressing this question, Noordermeer et al.…”
mentioning
confidence: 99%
“…In their neuroimaging study addressing this question, Noordermeer et al. (10) showed that a group of participants with ADHD/oppositional defiant disorder had greater volumetric reductions in frontal regions than an ADHD-only group. They therefore suggested that the overlap of affected regions between commonly comorbid disorders may create a structural “double burden” in those areas.…”
mentioning
confidence: 99%